2022
DOI: 10.1177/10451595221129658
|View full text |Cite
|
Sign up to set email alerts
|

Women Academics’ Learning as a Result of Being Bullied

Abstract: Like other workplaces, bullying occurs in academia. Additionally, women report more frequent and severe forms of bullying than men. The purpose of this qualitative study was to unearth women academics’ learning because of being bullied. We discuss the learning context and explore the learning that occurred. Understanding these factors can augment the literature on bullying in academia. As a result of being bullied, women fundamentally changed their perceptions of themselves, others, their respective institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Although this gender pattern is by no means unique (with women represented among bullies and men among their victims), this envy seems to take a particularly virulent form in the bullying of women by men. The research literature on bullying reveals a high prevalence of women, often exceptional women, among those who are bullied (Baumgartner, Zarestky & Lechuga, 2022). As the 1904 cases analysed by Sherry Moss and Morteza Mahmoudi (2021) demonstrate, a specific targeting of women academics is common, in part because of their precarious positions, combined with rigid enforcement of metricised performance management and associated surveillance (Gill, 2014).…”
Section: Envy Spoiling and Coercive Controlmentioning
confidence: 99%
“…Although this gender pattern is by no means unique (with women represented among bullies and men among their victims), this envy seems to take a particularly virulent form in the bullying of women by men. The research literature on bullying reveals a high prevalence of women, often exceptional women, among those who are bullied (Baumgartner, Zarestky & Lechuga, 2022). As the 1904 cases analysed by Sherry Moss and Morteza Mahmoudi (2021) demonstrate, a specific targeting of women academics is common, in part because of their precarious positions, combined with rigid enforcement of metricised performance management and associated surveillance (Gill, 2014).…”
Section: Envy Spoiling and Coercive Controlmentioning
confidence: 99%
“…Alfred (2021), Barker (2021), Reneau and Brooks (2020) Incorporating intersectionality into adult learning and education. Baumgartner et al (2022), Brookfield (2003), Tharp (2017), Thériault (2019) As readers of the literature, we recognize the impact of the researcher's social identities and experiences on intra-acting with the texts (Lens Taguchi & Parlmer, 2013). We appreciated the entangled positionality and research experiences of the three authors throughout the research process.…”
Section: Key Themes Authorsmentioning
confidence: 99%
“…Adult bullying should not happen for sure, but in some cases, adult bullying experiences were found to lead to transformative learning. Based on the interviews of 11 women professors from multidiscipline and multi-races, Baumgartner et al (2022) found that the women professors experienced transformative learning as a result of being bullied in academia (e.g., bodily bullying, exclusion, emotional burden) since their perceptions and worldviews were changed positively or negatively. After being bullied, some women professors learned to value themselves, changed priorities (e.g., began enjoying life more than pleasing others) and gained compassion for others, although bullying certainly had a negative effect (e.g., worsened viewpoints of the world, including themselves, others, and institutions).…”
Section: Intersectional Experiencesmentioning
confidence: 99%
See 2 more Smart Citations